Bank Regulation and Bank Crisis - Sigbjørn Atle Berg; Øyvind Eitrheim (Norges Bank, 2009)
The Norwegian experiences of the past thirty years illustrate what we believe are two general tendencies in bank regulation. The first one is that a bank crisis will tend to focus regulators' minds and lead to stricter regulations. The second one is that cycles in regulation tend to interact with the economic cycle, in the sense that the rationale for strong regulation tends to become somewhat blurred when the economy is booming. These patterns appear in the Norwegian experience after the banking crisis of 1988-92, and they can presumably also be recognized in many other jurisdictions.
hdl:11250/2497623
Keywords: G28; N44; 330; Basel I & II; banking crises; history of bank regulation; capital adequacy